Deflectometric measurement of large mirrors - Olesch, Evelyn; Häusler, Gerd; Wörnlein, André; Stinzing, Friedrich; van Eldik, Christopher (Advanced Optical Technologies, 2014)
We discuss the inspection of large-sized, spherical mirror tiles by 'Phase Measuring Deflectometry' (PMD). About 10 000 of such mirror tiles, each satisfying strict requirements regarding the spatial extent of the point-spreadfunction (PSF), are planned to be installed on the Cherenkov Telescope Array (CTA), a future ground-based instrument to observe the sky in very high energy gamma-rays. Owing to their large radii of curvature of up to 60 m, a direct PSF measurement of these mirrors with concentric geometry requires large space. We present a PMD sensor with a footprint of only 5 ?2 ?1.2 m3 that overcomes this limitation. The sensor intrinsically acquires the surface slope; the shape data are calculated by integration. In this way, the PSF can be calculated for real case scenarios, e.g., when the light source is close to infinity and off-axis. The major challenge is the calibration of the PMD sensor, specifically because the PSF data have to be reconstructed from different camera views. The calibration of the setup is described, and measurements presented and compared to results obtained with the direct approach.
Keywords: 3D-metrology; Deflectometry; Interferometry; Optical testing; Telescope